Pharmaco-Therapeutic Study Of Shankhpushpiyadi Yog (Kalpit Yog) In Management Of Manoavsad W.S.R. To Mental Depression: A Research Article - Sharma, Mayukh; Singh, Chandan; Adlakha, Manoj (International Research Journal of Ayurveda & Yoga, 2020)
Ayurveda is one of the world’s most ancient medical sciences. Ayurveda originating from Vedas is an eternal medical science that covers all aspects of life, health, disease, and therapy. Ayurveda is regarded Atharvaveda’s Upaveda and thus has its birthplace from Vedas, the earth’s oldest recorded wisdom. Darshana’s spirit is the basic foundation of Ayurvedic values. Dharma, Artha, Karma and Moksha are the primary objectives of life that constitute the root cause of health. The human life has been regarded the invaluable opportunity to accomplish all these stuff and one requires a good and peaceful life. Our ancient society’s goal was to accomplish these objectives by having a soft, sound, calm, steady and healthy lifestyle. On the other side, in today’s modern era life has become so advanced that modifications in lifestyle and dietary habits along with over-ambitiousness lead to enhanced mental depression, which acts as a predisposing factor to trigger multiple psychological disturbances and mental disorders. Therefore, today’s metaphysical society faced stressful circumstances and changed the lifestyle every day. As a consequence, anxiety, depression, insomnia, stress-related disorders and other mental illnesses come into being like forest fire, and the present era has become an age of psychiatric problems. Shankhpushpi (Convolvulus pluricaulis, fam. Convolvulaceae), Mandukparni (Centella asiatica, fam. Umbelliferae), Jyotishmati (Celastrus paniculatus, fam. Celastraceae), Tagara (Valeriana wallichii, fam. Valerianaceae), Jatamansi (Nardostachys jatamansi, fam. Valerianaceae) & Ashvagandha (Withania somnifera, fam. Solanaceae) have been traditionally used in mental disorders. In this chapter consists of detailed conceptual study regarding the plant Shankhpushpi (Convolvulus pluricaulis), Mandukparni (Centella asiatica), Jyotishmati (Celastrus paniculatus), Tagara (Valeriana wallichii), Jatamansi (Nardostachys jatamansi) & Ashvagandha (Withania somnifera) with literary review compiled from various Floras and Materia medica, a detailed information about these plants, its medicinal uses, botanical description comprising vernacular names, habit, habitat, morphological characters, distribution, officinal part and chemical constitution. The study entitled “Pharmaco-Therapeutic Study of Shankhpushpiyadi Yog (Kalpit Yog) in Management of Manoavsad W.S.R. to Mental Depression” was undertaken as dissertation work for the degree of M.D. (Ayu.) under Dr. Sarvepalli Radhakrishnan Rajasthan Ayurved University, Jodhpur.